Destruction of Staphylococcus aureus and the impact of chlortetracycline on biomethane production during anaerobic digestion of chicken manure. Issue 11 (November 2019) - Kirby, M.E.; Mirza, M.W.; Leigh, T.; Oldershaw, L.; Reilly, M.; Jeffery, S.
Abstract: Research was undertaken to ascertain the effect on biogas potential during the anaerobic digestion of chicken manure containing Staphylococcus aureus and chlortetracycline (antibiotic) from infected chicken flocks. S. aureus is a pathogenic bacteria in chicken flocks that is usually treated with the broad-spectrum antibiotic, chlortetracycline. Veterinary antibiotics are often prescribed in the poultry sector for on-farm use at the flock level to control disease; consequently, significant quantities of antibiotics are excreted from the bird into the manure. Subsequent anaerobic digestion of this chicken manure could lead to pathogens and antibiotics affecting the digestion process. Anaerobic digestion biochemical methane potential assays were completed at 35°C for 39 days, with some assays receiving S. aureus and some receiving S. aureus and chlortetracycline. No viable S. aureus cells were detected after Day 0 of the experiment. A further experiment utilising an order of magnitude greater concentration of S. aureus demonstrated a significant reduction (>400 fold) in S. aureus within 24 h when inoculated into anaerobic digestate, with no viable S. aureus cells detected by the end of 3 days. Furthermore, the efficacy of chlortetracycline was significantly reduced when applied to anaerobic digestate compared to water alone. Total biogas yields from chicken manure were significantly lowered by the addition of S. aureus, with and without chlortetracycline. However, there was no significant difference in methane yields between treatments. The cellulose control assays showed a lag phase in methane production after receiving chlortetracycline. In comparison, the absence of a lag phase when the antibiotic were added to chicken manure may have been due to the relatively high nitrogen content of the feedstock reducing the inhibition of chlortetracycline on methanogens. Therefore, this study demonstrates that the addition of S. aureus and chlortetracycline does not have a commercially relevant effect on the digestion of chicken manure. Abstract : Microbiology; Bioenergy; Wastewater Management; Antibiotics; Anaerobic Digestion; Staphylococcus aureus; chlortetracycline; biochemical methane potential; chicken manure